2015
DOI: 10.3109/01676830.2015.1057292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Upper Eyelid Blepharoplasty on Vision and Corneal Tomographic Changes Measured By Pentacam

Abstract: We discovered statistically significant astigmatic changes; however, these were clinically insignificant visual acuity changes in compatibility with prior studies. Patients undergoing blepharoplasty surgery should be advised that this procedure may potentially alter vision. It is also very important to advise the patients to undergo cataract and/or refractive surgery after having upper eyelid surgery that this procedure may induce vision changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 17 publications
1
36
0
2
Order By: Relevance
“…According to Zinkernagel et al 15 , significant keratometric changes occured after upper eyelid blepharoplasty in patients with severe dermatochalasis who required adipose tissue excision. Şimşek et al 16 and Altın Ekin et al 17 observed statistically significant changes in astigmatism after surgery, but reported that this difference did not influence visual acuity levels. Doğan et al 18 reported that upper eyelid blepharoplasty did not affect keratometric values.…”
Section: Discussionmentioning
confidence: 97%
“…According to Zinkernagel et al 15 , significant keratometric changes occured after upper eyelid blepharoplasty in patients with severe dermatochalasis who required adipose tissue excision. Şimşek et al 16 and Altın Ekin et al 17 observed statistically significant changes in astigmatism after surgery, but reported that this difference did not influence visual acuity levels. Doğan et al 18 reported that upper eyelid blepharoplasty did not affect keratometric values.…”
Section: Discussionmentioning
confidence: 97%
“…Eyelid position has been found to be an important factor contributing to the aberration changes [4,5,[13][14]. For objective visual quality changes in ptosis, nearly all studies have focused on the differences in lower-order aberration between ptosis eyes and normal eyes [15][16][17][18] and only a few researches have aimed at the HOAs changes in ptosis eyes. However, there are still no studies investigating the corneal HOAs and intraocular scatter changes in ptosis eyes.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 21 Different aspects of the cornea show different characteristics in normal and pathological conditions. For example, some studies 22 , 23 have shown alterations in the corneal topographies of dermatochalasis patients. Other studies have revealed corneal biomechanical changes in diseases related to connective tissue and skin, such as MS and FES.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies 22 , 23 have been conducted on corneal topography in an attempt to explain the improved visual functions expressed by patients following surgical treatment of dermatochalasis. These studies mainly show clinically insignificant, but statistically relevant, corneal topographic alterations.…”
Section: Discussionmentioning
confidence: 99%